Brain Metastasis of Nasopharyngeal Carcinoma: A Case Report and Literature Review. (20th February 2012) - Kaidar-Person, Orit; Kuten, Jonathan; Atrash, Fadi; Billan, Salem; Kuten, Abraham
Abstract : Central nervous system metastases from nasopharyngeal carcinoma (NPC) are uncommon. The patient presented was diagnosed with aggressive advanced NPC resistant to treatment and complicated by a solitary brain metastasis. A PubMed database search was conducted to review the existing literature regarding brain metastases of NPC, using the search terms "nasopharyngeal neoplasia, " "nasopharyngeal carcinoma, " "nasopharynx, " "radiotherapy, " "central nervous system, " and "brain" in section of "Title/Abstract." The articles were first evaluated by title and then by abstract, and thereafter appropriate manuscripts were evaluated by full text. References of the published papers were also reviewed.